2022
DOI: 10.21203/rs.3.rs-1307573/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primary Ventricular Fibrillation as The First Presentation of Aortic Dissection: A Case Report

Abstract: This study is about an infrequent first presentation of Aortic Dissection (AD), and it is primary Ventricular Fibrillation (VF). We present a 64-year-old woman with a history of hypertension who came with sudden retrosternal chest pain, dizziness, nausea, and vomiting. The patient suffered a cardiac arrest a few seconds after admission. Cardiopulmonary resuscitation (CPR) was done for her. An electrocardiogram (ECG) showed ST elevation that demonstrated acute anterior MI (Myocardial Infarction). Trans-thoracic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Timely imaging is vital for diagnosis, especially in hemodynamically unstable patients [ 10 ]. CTA is the gold standard for diagnosing aortic syndromes, however, MRI and echocardiography also have utility [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timely imaging is vital for diagnosis, especially in hemodynamically unstable patients [ 10 ]. CTA is the gold standard for diagnosing aortic syndromes, however, MRI and echocardiography also have utility [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients must be followed serially with imaging due to the unpredictable nature of AIH. In some cases, the hematoma can propagate within the false lumen of the aortic wall and interfere with the heart’s physiologic properties, as described in Gheshlaghi et al’s report [ 10 ]. Recent reviews have also found worsening outcomes to be associated with radiologic findings of proximal migration of the hematoma, hematoma thickness >11 mm, aortic diameter >50 mm, progressive aortic enlargement, ulcer-like projections, focal intimal disruption, and poor blood pressure control [ 1 , 13 ].…”
Section: Discussionmentioning
confidence: 99%